PERFORMANCE ANALYSIS OF THE CITY AIRPORT: A Case Study of Halim Perdanakusuma to be Jakarta City Airport - PAHALA, FITRADY ([Yogyakarta] : Universitas Gadjah Mada, 2015)
This research attempts to determine the potentiality of Halim Perdanakusuma Airport as Jakarta City Airport in the future. The performance analysis of city airport took place on Halim and Soekarno-Hatta based on the assumption that the airports have similar catchment areas and are located in similar geographical locations. The methods of performance analysis is used to assess the airport performances at Halim Airport compared with Soekarno-Hatta Airport as the main airport that serves Jakarta City. Some important key factors will be carefully examined, such as traffic, airport throughput performances, airport infrastructures, airport charges, airlines operations, airport economic and financial performances, catchment areas, accessibility to airports, and environmental issues related to airport operations. The preliminary research findings have shown that Halim must be able to accommodate 3,9 million to 6 million passenger over the next five years, and the passenger terminal needs to be expanded. The final results, the current problem of mix traffic that impacted in a runway occupancy time problem should be overcome by developing new parallel taxiway at the north side of the runway. Because the Angkasa Pura as the airport company actually knows the prospects of Halim, then as the consequence, a similar amount of the airport charges has been applied similarly as the main airport Soekarno-Hatta. Furthermore, Halim could be also losing its attractiveness due to environmental issues relative to its location near city centre, such as road congestion and flooding near the surroundings of the airport. The airport surface access still needs improvement by providing multi-modes transport access directly to the airport terminal. The impact of water over-spillage from the two rivers that caused flooding in the surrounding airport environment should be minimised by building several reservoirs and drainages. The involvements and work cooperations with the other stakeholders and policy makers are needed to overcome those issues. Finally, based on the performance analysis results on both Halim and Soekarno-Hatta, this research has identified some aspects and performances of Halim Airport that are feasible for further development and several recommendations have been delivered to show Halim Airport to be Jakarta City Airport in the future.